Ethical climate in the New Zealand health sector - Mirshekary, S.; Yaftian, A.; Brown, Alistair; Chatterjee, Bikram (Inderscience Publishers, 2012)
The paper investigates the ethical climate in the New Zealand health sector after it experienced heavy reform. The findings of the study suggest that little emphasis has been placed on ethics in the New Zealand public health sector. Apart from individuals’ own professionalism and intrinsic motivation there appear to be no incentives for employees to show exemplary ethical behaviour. This is because there is no reward to show exemplary ethical behaviour and report ethics related issues. There also appears to be a tendency for the public health organisations to set a formal code of ethics and core values instead of detailed guidelines and creating an environment of motivation to act ethically.